Alteraciones cardiovasculares inducidas por el veneno de Lachesis muta (Serpentes:Viperidae) y por su enzima fibrinogenolítica - Granados-Zúñiga, Jorge; Aragón-Ortíz, Federico (Revista de Biología Tropical, 1998)
Te fibrinogenolytic activity of Lachesis muta stenophyrs venom was studied. Wistar rats catheterized at carotid artery and jugular vein were inoculated with crude venom or enzyme and changes in arterial pressure, cardiac frequency and electrocardiogram we monitored. The enzyme induced a greater fibrinogen reduction t the crude venom without any cardiovascular or histological alteration. I vitr crude venom coagulated blood whereas the enzyme reduced fibrinogen in 23%. Results suggest the potential use of the fibrinogenolytic enzyme as antithrombotic agent.